Design of Chassis Frame for All-Terrain Vehicle for Educational Purposes - Hassan, Muhammad Zahir; Abdul Munir, Fudhail; Salim, Mohd Azli (Trans Tech Publications, Switzerland, 2015)
All-terrain vehicle is famously used for various purposes. The design of the chassis of this vehicle is critical in determining the overall strength. In this paper, the design chassis frame for the use of all-terrain vehicle (ATV) is presented. In designing the chassis frame, a proper design method was employed. Finite Element Analysis (FEA) was utilized to determine the maximum stress and displacement of the frame when a particular load is applied onto it. Structure modifications need to be done if the chassis frame could not sustain the applied load. After the design process is completed, the fabrication of the frame is conducted by students of the engineering faculty. The fabricated frame will be used as the main part for a project of which a complete ATV will be developed. The main purpose of the project is to instill the interest among the student in engineering through the application of classroom.